A Time-Motion Analysis of Lightweight Women's Judo in the 2010 World Championships. Issue 2 (June 2015) - Challis, Darren; Scruton, Adrian; Cole, Michael; Callan, Michael
The Olympic sport of judo has a growing base of performance analysis research considering the technical aspects, the tactical aspects and time motion analysis. This study aimed to further analyse this sport by specifically considering the time motion aspects of work, rest, kumi-kata and ne-waza in lightweight women's judo to establish if there are differences in this specific population of judo athletes. Pre-recorded footage of the women's u48kg, u52kg and u57kg weight divisions (143 contests) from the 2010 world judo championships were coded into temporal sequences. The coding of five KPIs across the three weight groups produced a total of 1756 hajime to matte blocks (work), 1422 matte to hajime blocks (rest), 1786 kumi-kata sequences (gripping sequences), and 516 ne-waza sequences (ground work). The results suggest the time spent in hajime to matte (work) and in matte to hajime (rest) are similar to those seen in other studies. This suggests there is little difference in the work to rest segments for lightweight women's judo compared to heavier weights and males.